Gender Justice and Feminist Politics: Decolonizing Collaborative Research - Dolores Figueroa Romero (Genealogy, 2023)
The most prominent social effects of the drug war in Mexico are the criminalization of poverty and increased rates of feminicide. Feminist academics and community leaders have been developing and working hand in hand to find the most appropriate methods to document gender-based violence and feminicide to shed light on the impunity that hides the systemic dismissal of women’s lives. This essay presents a critical analysis of my own positionality as a feminist and academic ally in building a collaborative research alliance with indigenous women leaders who are politically engaged in the production of knowledge from an intersectional perspective that adequately reflects the matrix of violence that affects the lives of indigenous women in urban and rural areas. This process has been fruitful and promising, although it has also entailed challenges and contradictions arising from disparate meanings of gender justice and the lack of encounter of feminist/indigenous politics of resistance.